Una pillola per diventare bambini buoni? Considerazioni sul disturbo da deficit dell’attenzione e iperattività - Bembina, Adriana; Della Putta, Daniela (Il sogno della farfalla, 2013)
The authors describe Attention Deficit-Hyperactivity Disorder( ADHD) from a clinical, epidemiological, historical and cultural point of view, focusing on the two main approaches present in the Italian debate. On the one hand, the neurological-organicist approach helps form the current guidelines adopted by the Istituto Superiore di Sanità regulating pharmacological therapies. On the other hand, public opinion is sensitive to the position of private associations made up of experts and parents, who interpret the behavior of distracted and hyperactive children as a mere “diversity”, and look forward expedients that facilitate a better social integration of these student. The vision of the child which arises from Massimo Fagioli’s birth theory and forms the basis of the clinical work of the authors is in direct contrast with the two above-mentioned approaches and will be further explored in a subsequent article.